PENERAPAN MODEL PROJECT-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI TERTULIS SISWA SMP PADA MATERI PENCEMARAN LINGKUNGAN - Dinda Ayu Rahmadani; Aris Rudi Purnomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students’ written communication skills, the implementation of learning activities, and students’ responses after the application of the Project Based Learning (PjBL) model on environmental pollution material. This research employed a pre-experimental method with a one-group pretest-posttest design. The research subjects consisted of 34 students of class VII-H at SMPN 43 Surabaya. The research instruments included a written communication skills test sheet, a learning implementation observation sheet, and a student response questionnaire. Data were collected through pretest, posttest, observation, and questionnaire. The data were analyzed using quantitative descriptive analysis. The results showed that the improvement in students’ written communication skills based on the N-Gain score was categorized as moderate (56%) and high (44%). The implementation of learning activities in each meeting was categorized as very good. Students’ responses to the implementation of the Project Based Learning model showed a high percentage and were categorized as very good. In conclusion, the implementation of the Project Based Learning model on environmental pollution material can improve students written communication skills.